2020
DOI: 10.2478/adms-2020-0015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on the Properties of Nickel Sulfide Films Performed by Spray Pyrolysis Technique

Abstract: In this work, we have prepared new materials of the nickel sulfide thin films by using the spray pyrolysis technique for promising co-catalyst to improve the photocatalytic performance or superconductivity. The effect of deposition temperature (523, 573 and 623 K) on structural, optical and electrical properties was investigated. The XRD diffraction shows that the prepared nickel sulfide at 523, 573 and 623 K having an orthorhombic, hexagonal and hexagonal structure, which were Ni3S2, Ni17S18 and NiS2, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 41 publications
(46 reference statements)
5
3
0
Order By: Relevance
“…Thus, confirming the metallic behavior of the prepared NiS, which support the above claim about the Moss-Burstein effect. Also, these results are close to the reported data in the literature [26,27]. It is evident that the NiS prepared in this study is highly attractive as an electrode material for application in supercapacitors.…”
Section: Electrical Studiessupporting
confidence: 91%
“…Thus, confirming the metallic behavior of the prepared NiS, which support the above claim about the Moss-Burstein effect. Also, these results are close to the reported data in the literature [26,27]. It is evident that the NiS prepared in this study is highly attractive as an electrode material for application in supercapacitors.…”
Section: Electrical Studiessupporting
confidence: 91%
“…These findings, derived from FTIR spectroscopy analysis, improve our understanding of the complex's chemical composition and provide insights into its unique bonding properties. Notably, the FTIR spectra at 1262 cm −1 displayed the occurrence of an amine functional group, which corresponds to the findings of Gahtar et al [ 30 ] Furthermore, a distinct CH 2 peak at 1490 cm −1 was observed, which is consistent with the findings of Mousavi‐Kamazani et al [ 31 ] Furthermore, Mousavi‐Kamazani et al [ 31 ] discovered an OH peak at 3445 cm −1 , which they attributed to absorbed atmospheric water. The detection of CH vibrations at 2960 cm −1 broadens our understanding of the complex diverse functional groupings, enriching its spectroscopic profile and allowing for a more in‐depth understanding of its chemical composition.…”
Section: Resultssupporting
confidence: 87%
“…The presence of a carboxylic group was demonstrated by a prominent stretching peak at 1266 cm À1 , as previously reported by Chen et al [35] and Ghogare et al [36]. After conducting a thorough investigation, Gahtar et al [37] discovered the existence of an amine functional group at 1084 cm À1 . The existence of a CH 2 peak at 1511 cm À1 in the FTIR spectrum was another noteworthy discovery that was consistent with the research done by Mousavi-Kamazani et al [38].…”
Section: Functional Groups Explorationsupporting
confidence: 63%